(untitled) (Environment & Health, 2022)
Objective: human health risk assessment and social costs from air pollution by industrial enterprises and vehicles emissions. Materials and methods: The study included 7526 emission sources of 37 different by economic activity industrial enterprises and vehicles (46 sections of roads and 14 intersections), located in different cities of Ukraine. Program complex ISC-AERMOD was implied in average 24-hour and annual pollutant concentrations calculations. Risk criteria assessment was completed according to approved U.S. EPA and WHO procedure of risk assessment. Results: Levels of non-carcinogenic risk (HQ) have been calculated in assessing acute (at the level of average daily concentration; HQacute=1.1÷7.9) and chronic (at the level of average annual concentration; HQchrohic=1.1÷8.5) inhalation effects of priority chemicals of industrial enterprises and vehicles on the health of exposed population of studied cities. It was found that, according to the WHO recommendations, the calculated levels of non-carcinogenic risks (HQ = 3.0÷6.0; HQ≥6) belonged to moderate and high levels of air pollution and could cause, respectively, weak and pronounced effects in vulnerable groups of the population (elderly people, pregnant women and children). The levels of total carcinogenic risk (ICRtotal) for exposed population have been assessed. It was determined that the possible social costs of the population in the form of additional probability of the development of tumors in the individual from the inhalation exposure of the studied groups of the industrial enterprises and vehicles could be from 9 cases per 10,000 population to 5 cases per 1,000 people. Conclusion: Research results are illustrating the significant impact of air pollution on human health and require implementation innovative methodological approaches implementation of the risk management stage in order to adopt rational (environmental and preventive) political decisions at the local, regional and national levels.